The Indirect Effect of Death Anxiety on Experienced Meaning in Life via Search for Meaning and Prosocial Behavior - Chang, Baorui; Cheng, Jiaxin; Fang, Jiandong; Dang, Junhua (Frontiers in Psychology, 2021)
This study investigated the relationship between death anxiety and experienced meaning in life. Six hundred and forty-eight Chinese college students were surveyed using the Death Anxiety Scale, the Prosocial Behavior Scale, and the Meaning in Life Scale. The results showed that death anxiety predicted experienced meaning through three pathways: the first one was through search for meaning singly; the second one was through prosocial behavior singly; and the third one was through search for meaning and prosocial behavior serially, which accounted for the highest proportion of the total effect. This study highlights the positive side of death anxiety.